Characterization and Functional Analysis of Mouse Semi‐invariant Natural T Cells. (3rd April 2017) - Kumar, Amrendra; Bezbradica, Jelena S.; Stanic, Aleksandar K.; Joyce, Sebastian
Abstract: Semi‐invariant natural killer T (iNKT) cells are CD1d‐restricted innate‐like lymphocytes that recognize lipid agonists. Activated iNKT cells have immunoregulatory properties. Human and mouse iNKT cell functions elicited by different glycolipid agonists are highly conserved, making the mouse an excellent animal model for understanding iNKT cell biology in vivo. This unit describes basic methods for the characterization and quantification (see Basic Protocol 1) and functional analysis of mouse iNKT cells in vivo or in vitro. This unit also contains protocols that describe enrichment and purification of iNKT cells, generation of CD1d tetramer, and lipid antigen loading onto cell‐bound and soluble CD1d for activation of NKT cell hybridomas. © 2017 by John Wiley & Sons, Inc.